Improvement of dielectric properties of polypropylene films for capacitors based on metal-ash suppression. (August 2022) - Du, Boxue; Zhang, Jianhang; Xiao, Meng; Liu, Haoliang; Ran, Zhaoyu; Xing, Jiwen
Abstract: In this paper, polypropylene (PP) composite films modified with the metal deactivator (MD) are prepared in order to suppress the adverse effect of metal ashes on the dielectric properties. The dielectric properties of samples are tested and the results show that the breakdown strength of the composite sample at 25, 55 and 85 °C is significantly enhanced, and the deterioration of the DC conductivity by the electrical field and heat is greatly weakened. The dielectric constant of the composite sample is slightly increased with the relatively low dielectric loss, and the discharge energy density is increased by 68%. Due to the complexation reaction between MD1024 and metal ashes, the catalytic effect of metal ashes on thermal-oxidative degradation is significantly suppressed, and the oxidation induction time (OIT) of the composite film is greatly increased to 40.5 min from 7.7 min of pure PP, which improves the thermal-oxidative stability of the composite sample. This study provides a feasible reference for the development of high-reliability PP films for capacitors. Graphical Abstract: ga1